La enfermedad como enigma: construcciones de sentido que atribuyen tres pacientes de cáncer a su enfermedad mediante el uso de metáforas - Ordóñez Molina, Alejandra (Universidad de San Buenaventura, Cali, 2019)
While the medical perspective operates technically on the disease excluding its subjectivity and expression of beliefs, values and social practices that they consider as obstacles that limit professional intervention. In illness, metaphor allows to create compact descriptions of sense in front of complex phenomena. Cancer appears as an explanation of mystical power, as supernatural punishment or as demonic possession; as the moral test of the behavior of the individual and society; as the impossibility of the individual to escape a destiny; as a means of redemption for the marginal; as a means of enhancing the awareness of death, spirituality and the complexity of life; and as an incomprehensible force that penetrates life and destroys. In this way, psychoanalysis recognizes the organic dimension of disease - the stewardess is also a medicine and medical intervention - also considers the dimension of unconscious content and difference in the biological organism and body - whose main characteristic is that of being sensitive to the word. Therefore, from the psychoanalytic clinic allows the patient with cancer to recognize their particularity against the dimension of a disease, the way it is posture in front of it and the possible treatments to which it recovers to cure.